Nanospan, an alternatively spliced isoform of sarcospan, localizes to the sarcoplasmic reticulum in skeletal muscle and is absent in limb girdle muscular dystrophy 2F - Angela K. Peter (Skeletal Muscle, 2017)
Abstract Background Sarcospan (SSPN) is a transmembrane protein that interacts with the sarcoglycans (SGs) to form a tight subcomplex within the dystrophin-glycoprotein complex that spans the sarcolemma and interacts with laminin in the extracellular matrix. Overexpression of SSPN ameliorates Duchenne muscular dystrophy in murine models. Methods Standard cloning approaches were used to identify nanospan, and nanospan-specific polyclonal antibodies were generated and validated. Biochemical isolation of skeletal muscle membranes and two-photon laser scanning microscopy were used to analyze nanospan localization in muscle from multiple murine models. Duchenne muscular dystrophy biopsies were analyzed by immunoblot analysis of protein lysates as well as indirect immunofluorescence analysis of muscle cryosections. Results Nanospan is an alternatively spliced isoform of sarcospan. While SSPN has four transmembrane domains and is a core component of the sarcolemmal dystrophin-glycoprotein complex, nanospan is a type II transmembrane protein that does not associate with the dystrophin-glycoprotein complex. We demonstrate that nanospan is enriched in the sarcoplasmic reticulum (SR) fractions and is not present in the T-tubules. SR fractions contain membranes from three distinct structural regions: a region flanking the T-tubules (triadic SR), a SR region across the Z-line (ZSR), and a longitudinal SR region across the M-line (LSR). Analysis of isolated murine muscles reveals that nanospan is mostly associated with the ZSR and triadic SR, and only minimally with the LSR. Furthermore, nanospan is absent from the SR of δ-SG-null (Sgcd−/−) skeletal muscle, a murine model for limb girdle muscular dystrophy 2F. Analysis of skeletal muscle biopsies from Duchenne muscular dystrophy patients reveals that nanospan is preferentially expressed in type I (slow) fibers in both control and Duchenne samples. Furthermore, nanospan is significantly reduced in Duchenne biopsies. Conclusions Alternative splicing of proteins from the SG-SSPN complex produces δ-SG3, microspan, and nanospan that localize to the ZSR and the triadic SR, where they may play a role in regulating resting calcium levels as supported by previous studies (Estrada et al., Biochem Biophys Res Commun 340:865–71, 2006). Thus, alternative splicing of SSPN mRNA generates three protein isoforms (SSPN, microspan, and nanospan) that differ in the number of transmembrane domains affecting subcellular membrane association into distinct protein complexes.